Pengoptimalan Pengolahan Singkong Menjadi Produk Pangan Dalam Meningkatkan Pendapatan Masyarakat Desa - Rois, Fatqu; C.P.Z, Chinthia (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The rice field farming system in the village is considered advanced, so there are almost no obstacles to its operation. Therefore, we took the object of cassava, which is a food ingredient that can be processed into snacks that can increase the income of the Jonggrang village community. Our service uses the PAR method. Based on the results of the service carried out with farmer groups and cassava farmers, economic value was added to the cassava harvest into a new product in Jonggrang village, namely changing cassava into a snack packaged into crispy gethuk. With this training program, we hope to help maximize the potential of cassava, which was initially only sold raw, and after carrying out the training program, the community can produce new processed products. Apart from providing innovation in cassava processing, we also show how to market through social media and marketplaces based on Islamic law.